Incidence of haematological malignancies by ethnic group in England, 2001–7. (14th September 2013) - Shirley, Megan H.; Sayeed, Shameq; Barnes, Isobel; Finlayson, Alexander; Ali, Raghib
Summary: The aetiology of most haematological malignancies is largely unknown. Studies of migrant populations can provide insights into the relative importance of genetic and environmental risk factors for these diseases. This study compares incidence rates in British Indians, Pakistanis, Bangladeshis, Black Africans, Black Caribbeans, Chinese and Whites in England from 2001 to 2007. We analysed 134 302 haematological cancer registrations with ethnicity obtained by linkage to the Hospital Episodes Statistics database. Mid‐year population estimates from 2001 to 2007 were used. Incidence rate ratios adjusted for age, sex and income were calculated, comparing the six ethnic groups to Whites and to each other. Whites had the highest rates for most subtypes. However, Blacks experienced more than double the incidence of plasma cell and mature T‐cell neoplasms compared to other ethnic groups. There were also significant differences in incidence between Indians, Pakistanis and Bangladeshis for Hodgkin lymphoma and mature B‐cell neoplasms and between Black African and Black Caribbeans for mature B‐cell and other lymphoid neoplasms (all P  < 0·001). Our results show that the risk of haematological cancers varies greatly by ethnic group, including within those groups that have traditionally been grouped together (South Asians and Blacks) with many of these differences not explicable by known risk factors.